2015
DOI: 10.1021/acs.nanolett.5b01619
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Stiffness and Nanoscale Spatial Organization of Cell-Adhesive Ligands Direct Stem Cell Fate

Abstract: One of the breakthroughs in biomaterials and regenerative medicine in the latest decade is the finding that matrix stiffness affords a crucial physical cue of stem cell differentiation. This statement was recently challenged by another understanding that protein tethering on material surfaces instead of matrix stiffness was the essential cue to regulate stem cells. Herein, we employed nonfouling poly(ethylene glycol) (PEG) hydrogels as the matrix to prevent nonspecific protein adsorption, and meanwhile covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
248
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(271 citation statements)
references
References 60 publications
10
248
1
2
Order By: Relevance
“…However, low seeding densities have been associated with upregulation of osteogenesis when MSC are cultured under neutral conditions, suggesting that the increased area available for cell spreading on low adhesion spots may also be advantageous [58]. Notably, the spacing of integrin binding ligands that govern cell-substrate adhesion is known to control MSC differentiation: sparser immobilisation of RGD peptide on the culture surface results in greater osteoblast formation [14,60,61]. This contrasts with our observation that osteogenic differentiation increases when integrin binding Coll I is printed at high formulation concentrations, emphasising the strong osteogenic stimuli provided by Coll I.…”
Section: Discussionmentioning
confidence: 99%
“…However, low seeding densities have been associated with upregulation of osteogenesis when MSC are cultured under neutral conditions, suggesting that the increased area available for cell spreading on low adhesion spots may also be advantageous [58]. Notably, the spacing of integrin binding ligands that govern cell-substrate adhesion is known to control MSC differentiation: sparser immobilisation of RGD peptide on the culture surface results in greater osteoblast formation [14,60,61]. This contrasts with our observation that osteogenic differentiation increases when integrin binding Coll I is printed at high formulation concentrations, emphasising the strong osteogenic stimuli provided by Coll I.…”
Section: Discussionmentioning
confidence: 99%
“…Schwarz theory does not consider effects of the polarization of the diffuse layer on the polarization of the Stern layer (Lyklema et al 1983;Ye et al 2015;Niu et al 2016). According to Lyklema et al (1983), the Stern layer is almost completely screened by the diffuse layer and hence the polarization of the diffuse layer cannot be ignored.…”
Section: A P P E N D I X Bmentioning
confidence: 99%
“…26 Polymers not only simply control the biomolecule characteristics, but studies have indicated that polymers have a variety of properties that can enhance cellular responses. To design a scaffold that can maximize the biomolecule function on sophisticatedly designed polymers for tissue engineering applications, there should be more practical and quantitative data analyses to understand the complex combinational effects of parameters derived from both biomolecules and polymers.…”
Section: Discussionmentioning
confidence: 99%